2013
DOI: 10.1155/2013/761537
|View full text |Cite
|
Sign up to set email alerts
|

AGR2 Predicts Tamoxifen Resistance in Postmenopausal Breast Cancer Patients

Abstract: Endocrine resistance is a significant problem in breast cancer treatment. Thus identification and validation of novel resistance determinants is important to improve treatment efficacy and patient outcome. In our work, AGR2 expression was determined by qRT-PCR in Tru-Cut needle biopsies from tamoxifen-treated postmenopausal breast cancer patients. Our results showed inversed association of AGR2 mRNA levels with primary treatment response (P = 0.0011) and progression-free survival (P = 0.0366) in 61 ER-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 14 publications
2
36
0
3
Order By: Relevance
“…[13][14][15] Interestingly, a worse DFS was also apparent in AGR2-positive luminal cancers with LN metastases but not in LN-negative cases. When adjusted for treatment and other prognostic factors, AGR2 was an independent prognostic factor, together with pT, pN, and HER2 status for DFS in node-positive luminal cancers.…”
Section: Figmentioning
confidence: 93%
See 2 more Smart Citations
“…[13][14][15] Interestingly, a worse DFS was also apparent in AGR2-positive luminal cancers with LN metastases but not in LN-negative cases. When adjusted for treatment and other prognostic factors, AGR2 was an independent prognostic factor, together with pT, pN, and HER2 status for DFS in node-positive luminal cancers.…”
Section: Figmentioning
confidence: 93%
“…11 Clinically, high AGR2 expression is associated with poor outcome in ER-positive cancers and hormonally treated breast cancers. 8,[12][13][14][15] It also correlates with lower Electronic supplementary material The online version of this article (…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the induction of agr2 expression by oestrogen or oestrogen-mimetics like tamoxifen, in post-menopausal women, agr2 expression also predicts poor responses [66], possibly through an AKT signalling pathway [67] or an EGFR-dependent pathway [68]. Although agr2 and/or agr3 expression are reported to be linked to oestrogens or androgens in some cancers, there are clearly hormone-independent pathways that trigger their induction in liver, colorectal, lung, and pancreas to name a few [17,69,70].…”
Section: Agr2 Gene and Protein Expression In Relation To Cancer Cell mentioning
confidence: 99%
“…Later, it was shown that AGR2 expression is directly stimulated by ER signaling (Salmans et al., 2013) and correlates with poor outcome of patients with ER‐positive breast cancer (Hrstka et al., 2010; Innes et al., 2006), which emphasizes the importance of estrogen receptors in the regulation of AGR2 expression. From a functional perspective, AGR2 was shown to promote tumor metastasis, cell survival, cell proliferation and resistance to therapy (Hrstka et al., 2013; Ramachandran et al., 2008; Wang et al., 2008). In addition to breast cancer, AGR2 was also detected in many other adenocarcinomas (Brychtova et al., 2011).…”
Section: Introductionmentioning
confidence: 99%